Kepemimpinan Demokratis Kepala Madrasah Dalam Mendorong Inovasi dan Program Unggulan Berbasis Nilai-Nilai Islam di MTs Ma’arif NU Buaran Pekalongan - Rama Akbar Wirasandika; Mutohharun Jinan (Jayapangus Press, 2026)
This study examines the role of democratic leadership of a madrasa principal in fostering educational innovation and developing Islamic values-based flagship programs at MTs Ma’arif NU Buaran Pekalongan. This research addresses challenges faced by madrasas, including limited resources and low levels of teacher innovation. A qualitative approach with a single case study design was employed. Data were collected through in-depth interviews, observations, and document analysis. The findings reveal that democratic leadership characterized by participatory decision-making, openness, and teacher empowerment plays a significant role in encouraging innovation and strengthening institutional programs. The developed innovations include Tahfidz Al-Qur’an programs, project-based learning, and integration of religious and digital literacy. In addition, the principal actively builds partnerships with stakeholders to support program sustainability. This study highlights that the integration of democratic leadership and Islamic values contributes to improving student motivation, strengthening institutional identity, and ensuring sustainable educational innovation in madrasas.